AN ANALYSIS OF SPEAKING ACHIEVEMENT OF EXTROVERT AND INTROVERT STUDENTS AT THE SECOND YEAR STUDENTS OF ISLAMIC EARLY CHILDHOOD EDUCATION STUDENTS OF STITNU SAKINAH DHARMASRAYA - Widia Siska (Universitas Labuhanbatu, 2022)
Personality is the part that influences student learning behavior. This behavior is significant in the teaching process. Two types of student personalities affect student learning behavior: open personality and closed personality. Students with available personalities are friendly, have many friends, and love to chat and collaborate with classmates. Meanwhile, students with introverted personalities tend to be quiet, shy, and aloof. This study intends to understand the spoken language scores of students with open and closed personalities. The sample from this study is 36 second-semester students of STITNU Sakinah Dharmasraya in the 2021/2022 academic year consisting of 18 students with open personalities and 18 students with closed personalities taken using stratified random sampling techniques. In collecting data, researchers used two types of research instruments. First is the personality test. The personality test aims to find the student's personality type between open and closed. The second is the speaking test which seeks to find the student's speaking score. The study results found that students with available personalities obtained good speaking scores (71. 66), and students with closed personalities received lower speech scores (49.55)